Effect of the CSFV NS5A protein on key proteins in the MAPK and PI3K-mTOR signaling pathways in porcine macrophages - Wang, Yidan; Zheng, Xiaoru; Yang, Yingying; Zhao, Xinru; Li, Min; Huang, Juan; Zhang, Qiaoya; Qin, Xiaobing; Yu, Ying; Pan, Qing; Cao, Zhi (Frontiers in Microbiology, 2025)
Classical swine fever (CSF) is a highly contagious disease caused by classical swine fever virus (CSFV). NS5A, a non-structural protein of CSFV, plays an important role in regulating viral replication and protein translation. The purpose of this study was to investigate the effects of the CSFV NS5A protein on key proteins in the mitogen-activated protein kinase (MAPK) and phosphoinositide 3-kinase (PI3K)-mechanistic target of rapamycin (mTOR) pathways in porcine macrophages. In this study, an NS5A lentivirus was constructed, and 3D4/21 cells were infected. The cells infected for 48 h were collected for proteomic analysis to screen the differential proteins in the two signaling pathways in the NS5A/control group, and the expression levels of key proteins were verified by Western blotting (Wb). CSFV NS5A lentivirus was successfully constructed and used to infect porcine macrophages, and 23 upregulated proteins and 16 downregulated proteins were found in the MAPK signaling pathway, whereas 5 upregulated and 15 downregulated proteins were found in the PI3K-mTOR signaling pathway. The results revealed that with increasing infection time, the expression of IKBKG, AKT1, CDC37, MAP3K2, and PKN2 decreased, whereas the expression of MAP3K7 and KRAS2 increased. The 3D4/21 cells infected with NS5A lentivirus and classical swine fever virus were inoculated, and the differential protein expression was verified via Wb. With increasing time, the protein expression levels of IKBKG and KRAS2 increased, whereas the protein expression levels of MAP3K7, MAP3K2, AKT1, CDC37, and PKN2 decreased. This study provides data for revealing the mechanism by which CSFV evades host antiviral immune clearance and has important scientific significance and potential application value.